Endoscopic pyloromyotomy for treatment of gastroparesis: A new standard or still an experimental approach - Vasatko, Martin; Evinova, Eva; Hugova, Kristina; Simkova, Dagmar; Yepishkina, Katerina; Amin, Sunil; Martinek, Jan (Best practice & research. Clinical gastroenterology, 2024)
Gastroparesis (GP) can be a severe and debilitating disease. Its pathophysiology is complex and not completely understood. Two principal mechanisms are responsible for the development of symptoms - gastric hypomotility and pylorospasm. Pylorus targeted therapies aim to decrease presumably elevated pyloric tone - pylorospasm. There is a growing body of evidence about their role in the treatment algorithm of GP. G-POEM (endoscopic pyloromyotomy) is an extensively studied pylorus targeted therapy. Its efficacy ranges between 56 and 80% and the number of recurrences among those with treatment effect seems low. G-POEM is a safe procedure with very low frequency of severe adverse events. At present, G-POEM should not be considered as an experimental approach and may be offered to all patients with refractory and severe GP. Nevertheless, G-POEM is not a first line treatment. Conservative measures such as diet modification and pharmacotherapy should always be tried before G-POEM is considered. Further research must focus on better patient selection as at present there are no standardized criteria. Functional imaging such as impedance planimetry (EndoFlip) may hold promise in this regard.
Keywords: Pylorus; Gastric Emptying; Recurrence; pyloromyotomie; vyprazdňování žaludku; lidé; pylorus; gastroparéza; výběr pacientů; recidiva; Gastroparesis; Patient Selection; Treatment Outcome; Pyloromyotomy; výsledek terapie; Humans